PENINGKATAN KOMPETENSI LITERASI DAN NUMERASI SISWA SMK ASWAJA MELALUI PROGRAM KAMPUS MENGAJAR ANGKATAN 7 - Iis Ni’matul Jannah (Nusantara Hasana Journal, 2025)
Literacy competencies enable learners to understand, evaluate and interpret information by linking it to the needs of themselves and their surrounding environment and to respond to the needs of society. Numeracy is an ability related to basic mathematics used in solving problems in life, analyzing, interpreting, predicting and drawing conclusions. The 7th Generation Teaching Campus Program emphasizes strengthening literacy and numeracy competencies in schools that are at levels 1 and 2. Therefore, the purpose of this study is to find out the 7th Generation Teaching Campus programs at SMK Aswaja and to find out the implementation of the 7th generation teaching campus program to improve student literacy and numeracy at SMK Aswaja. Data collection methods with interviews, observation and document analysis. The results of the program implementation show that the work program includes making mading and posters, literacy and numeracy trees, playing educational videos, habituation of 15 minutes of literacy / reading books before the lesson takes place, number puzzle games, making reading corners, and revitalizing libraries, basic Microsoft training, training and CV making, repairing UKS, making toga gardens and QR codes, and making liquid and organic fertilizers. The results of the 7th batch teaching campus program on students' literacy and numeracy skills at SMK Aswaja are able to improve the ability of students to read and write.